Thermomechanical response of an ultrafine-grained nickel-yttrium alloy. (October 2020) - Srinivasan, S.; Kale, C.; Hornbuckle, B.C.; Darling, K.A.; Peralta, P.; Solanki, K.N.
Abstract: Thermomechanical behavior of an ultrafine-grained nickel-yttrium alloy has been investigated through quasi-static (10 −4 s −1 ) and high temperature creep experiments under uniaxial compression along with post-deformed transmission electron microscopy (TEM) characterization. While the alloy possesses a quasi-static flow stress of 1255 MPa at room temperature, the flow stress drops by about 80% at 873 K. TEM analysis showed negligible average grain growth over the entire temperature range tested. Furthermore, the alloy showed exceptional steady–state creep behavior owing to the relative stability of the grain size and interactions between dislocations/grain boundary and inclusions/dispersoids. Graphical abstract: Image, graphical abstract